A Well-Trained Team During Anaphylactic Shock After Rocuronium in a Patient With Aortic Stenosis: A Case Report - Macharadze, Tamar; Davies, Andrew; Fedor, Igor (Frontiers in Medicine, 2020)
A 66-year-old patient with aortic stenosis was scheduled for an aortic valve replacement and coronary artery bypass surgery. Anesthesia was induced by intravenous injection of midazolam, fentanyl and propofol. After administration of rocuronium, he developed an anaphylactic shock, which was diagnosed by clinical signs, vital parameters and not responding to the usual vasopressors. After thirty minutes of cardiopulmonary resuscitation the patient survived without any neurological deficits. This case is a reminder that early recognition and treatment of intraoperative hypersensitivity reactions is imperative. As well anesthetists should receive simulation training to achieve adequate experience in a safe environment. With well-trained team it is possible to save the life even of patients with aortic stenosis.